"The Relationship between Therapeutic Exercises and Functional Changes in the Musculoskeletal System in Patients with Low Back Pain and Knee Stiffness" (Comprehensive Journal of Science, 2026)
This study aimed to investigate the relationship between therapeutic exercises and functional changes in the musculoskeletal system among patients with low back pain and knee stiffness. A total of 30 participants were divided into an experimental group, which underwent an 8-week structured therapeutic exercise program, and a control group, which received standard care without specific exercises. The program included stretching, strengthening, balance, and functional exercises designed to enhance muscle strength, joint flexibility, and motor balance.Results indicated significant improvements in the experimental group compared to the control group, including a reduction in chronic pain, increased muscle strength, improved knee range of motion, and enhanced functional balance. Correlation analysis revealed a positive relationship between muscle strength, joint flexibility, and functional performance, and a negative correlation between pain and daily activity performance, suggesting that therapeutic exercises contribute to comprehensive musculoskeletal functional improvements.The study concluded that structured therapeutic exercises are effective in enhancing muscle strength, joint flexibility, and motor balance, positively affecting daily functional performance and reducing pain. It recommends implementing integrated exercise programs, long-term patient follow-up, combining other physiotherapeutic interventions, and providing patient education to sustain results and improve quality of life.
Keywords: therapeutic exercises, low back pain, knee stiffness, muscle strength, flexibility, motor balance